HYGIENIC ASPECTS OF TOBACCO SMOKING AMONG HEALTHCARE WORKERS, INCLUDING IN PRIMORSKY KRAI. A PILOT PROJECT TO REDUCE TOBACCO USE AMONG HEALTHCARE WORKERS - Alenitskaya, Marina Vladimirovna; Tokareva, Elvira Olegovna (Medicine in Kuzbass, 2026)
Smoking remains the leading preventable cause of death from chronic non-communicable diseases, including malignant tumors. The review examines the concept of reducing the harm caused by smoking (tobacco harm reduction) as an additional strategy for cancer prevention. Based on data from epidemiological, clinical, and laboratory studies, it has been shown that reducing the tar content in cigarettes, as well as switching to electronic nicotine delivery systems (ENDS) and tobacco heating systems (THS), significantly reduces exposure to carcinogenic and toxic substances. This leads to a decrease in the incidence and mortality from smoking-related cancers, particularly lung cancer, including among medical professionals in Primorsky Krai.The aim of the study was to substantiate the need to develop a regional tobacco control program for healthcare personnel.Materials and Methods. This article presents the results of an anonymous survey of 780 healthcare workers (327 physicians and 453 mid-level medical workers) from state healthcare organizations in Primorsky Krai.Results. According to the analysis, there is a high prevalence of smoking (23%), especially among male doctors (55%), as well as a lack of awareness about methods of treating tobacco addiction and support for the idea of introducing a ban on smoking and creating specialized rooms.Conclusion. Based on the data, conclusions were formulated about the need for a systematic regional program, and a pilot project was presented that should be implemented in Primorsky Krai. Medical professionals should use their own example to motivate patients to lead a healthy lifestyle.
Keywords: tobacco smoking; prevalence; medical professionals; questionnaire survey; regional program; staff health